The spectrum of congenital heart defects among children at federal medical centre, Asaba, Nigeria - Okwundika, Ifeoma O.; Ajaegbu, Obinna C.; Ighbosewe, Peace A.; Ezeonwu, Bertilla U.; Mbagwu, Nkemjika E.; Sadoh, Wilson E. (International Journal Of Community Medicine And Public Health, 2024)
Background: Congenital heart disease (CHD) is a common problem in the pediatric age group with significant morbidity and mortality when early diagnosis and prompt treatment are not instituted. Recent reports have shown an increasing burden of this disease. This study was aimed at documenting the prevalence and patter of CHD among children at Federal Medical Centre (FMC), Asaba. Methods: This was a hospital based retrospective observational study. The records of all children seen at the department of pediatrics FMC Asaba who did cardiac echo-cardiogram between 2019 and 2022 were reviewed. The clinical, demographic and echocardiogram details were retrieved, descriptive analysis was done using Statistical Package for Social Science (SPSS), version 21. Results: A total of 324 children were identified to have CHD of which 178 (54.9%) were male and 146 (45.1%) were female given a male to female ration of 1.2:1. Ventricular septal defect (27.7%) was the most common congenital heart disease seen while tetralogy of fallot 25 (7.7%) was the most prevalent cyanotic congenital heart disease. Trisomy 21 (5.5%) was the most frequently identified chromosomal abnormality identified among the subjects. A total of 61 (18.8%) of the subject died. Conclusions: The spectrum of CHD in our study was largely similar to previous documentation in the literatures. The mortality rate among children with CHD in our environment is still high largely due to non-availability of surgical intervention.